Analisis Tingkat Resiko Bahaya Muskuloskeletal Aktivitas Industri Kecil Makanan di Yogyakarta - Dewi, Luciana Triani (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
The study was originated from the result of observation on production activity of small food industries in Yogyakarta that showed varied awkward postures. Awkward posture will lead continual static loading on soft tissue which potentially cause musculoskeletal disorders and further will affect worker productivity and performance. The aim of the study was to analyze the risk level of musculoskeletal hazard among small food industries in Yogyakarta. The subjects of this study were 112 jobs performed in 16 small food industries in Yogyakarta. Risk level assessment used Baseline Risk Identification of Ergonomic Factors (BRIEF) Survey checklist which evaluate musculoskeletal risk of 9 body parts include posture, force, duration and frequency. The result of this study revealed 38 jobs (33.9%) without high level risk of all body parts and 74 jobs (66.1%) with high risk level in at least one body part. The highest prevalence of high risk level was for neck (36 jobs) and the highest prevalence of low risk level was for left elbow (79 jobs). Statistical analysis showed that there was significant difference of musculoskeletal risk level among 16 industries observed. The study recommended the awareness and proper hazard control to the industries.